“Programa sensorial-auditivo para disminuir el impacto ambiental causado por los altos niveles sonoros en las ciudades de morales, Tarapoto y Banda de Shilcayo en el año 2014” - Alvarado Rengifo, Romano Rai (2015)
In order to design a sensory-hearing program based on the principies and laws derivad from theories Conde Marin and Gimeno to reduce the environmental impact caused by high noise levels in the cities of Morales, Tarapoto and Shilcayo. The following problem arises: how a sensory-hearing program based on the principies and laws derived from the theories Conde Marin and Gimeno decrease the environmental · impact caused by high noise levels in the city of Morales, Tarapoto and Shilcayo? After application of the instruments of data collection, a survey of the population of the three districts in during the months of June and July 2014, results in the finding that: the perception in relation to high levels of noise noise firstly the population distribution is explained, then its impact on the physical, emotional and productive level. Strategy and methodology for the implementation of the proposal based on the principies and laws derived from the theories of Conde Marin, Gimeno is presented to reduce the environmental impact caused by high noise levels propases a process of interdependence between different Community strata ranging from emotional stability, ahd cooperative learning environment. Research has shown that the unification of criteria in a training environment and the community results automatically increased social interactions between people and changing attitudes (Terpstra and Tamura, 2008). Add or incorporate a program of social skills and social interaction in a community program.